2013
DOI: 10.1016/j.fsi.2013.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiles of toll-like receptors in channel catfish (Ictalurus punctatus) after infection with Ichthyophthirius multifiliis

Abstract: Toll-like receptors (TLRs) play a crucial role in the innate immune system, but to date the roles of fish TLRs in response to parasitic infection are still poorly understood. In the present study, we used channel catfish (Ictalurus punctatus) and the ciliate parasite Ichthyophthirius multifiliis as a model to investigate whether and which fish TLRs play important roles in the immune response against parasitic pathogens by detecting the expression profiles of a complete set of TLRs in catfish at different time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 41 publications
5
41
1
Order By: Relevance
“…Similarly, Zhang and colleagues reported upregulation of catfish TLR18 in spleen and liver tissue 4 h following immersion challenge with the enterobacterium, Edwardsiella ictaluri [35]. In contrast, TLR18 transcription was not changed in channel catfish infected with the ciliate parasite Ichthyophthirius multifiliis [36] and in the present study TLR18 transcription was not affected or was down regulated in kidney of ISAV infected salmon or trout with clinical PKD, respectively (Figs. 7 and 8A).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Similarly, Zhang and colleagues reported upregulation of catfish TLR18 in spleen and liver tissue 4 h following immersion challenge with the enterobacterium, Edwardsiella ictaluri [35]. In contrast, TLR18 transcription was not changed in channel catfish infected with the ciliate parasite Ichthyophthirius multifiliis [36] and in the present study TLR18 transcription was not affected or was down regulated in kidney of ISAV infected salmon or trout with clinical PKD, respectively (Figs. 7 and 8A).…”
Section: Discussionsupporting
confidence: 68%
“…7 and 8A). With respect to TLR19, catfish infected with I. multifiliis exhibit elevated TLR19 transcription in skin and gill tissues relative to uninfected controls [36], whilst T. bryosalmonae infected trout with severe kidney pathology exhibited significant up-regulation of TLR19 in trunk kidney tissue (Fig. 8A).…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested spleen was the main immune organ expressing TLRs in goldfish during D. intermedius infection. While the observations were not entirely consistent with the results of Zhao et al (2013), who detected that TLR genes distributed widely in tested tissues after infection with Ichthyophthirius multifiliis, however, expressing relatively higher in skin and gill. One possible reason for this variation is that parasite species and parasitic site is different from that of Zhao et al, and perhaps fish species also lead to TLR genes to express different among tissues.…”
Section: Resultscontrasting
confidence: 74%
“…What's more, the majority of researches on fish were focused on the roles of fish TLRs in the response to bacterial and viral infections, while the studies on their functions in parasitic infection were relatively insufficient. Recently, Zhao et al (2013) demonstrated that TLR1, TLR2, TLR9, TLR19, TLR21, and TLR25 of catfish played crucial roles in the immune response against Ichthyophthirius multifiliis infection. Besides, other studies have proved that TLR2, TLR9, and TLR21 of Epinephelus coioides were involved in anti-Cryptocaryon irritans immune defense (Li et al, 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al 60 examined TLR responses in several tissues (including skin and gill) following infection with the ciliate parasite Ichthyophthirius multifiliis. They reported significant upregulation of TLR1 in skin, and TLR2, TLR9, and TLR19 in skin and gill.…”
Section: Tlrsmentioning
confidence: 99%